Transfer of green-зелений colour meaning in English and Ukrainian fiction - Lukianets, Halyna (My University, 2018)
The article deals with transfer of English green and Ukrainian зелений colour terms meanings in literary texts. It is established that colour presentation scheme in the poetry and prose is designated by colour terms not only in their primary meaning, but also in secondary one, created as the result of semantic transfer based on resemblance and contiguity, and represented by colour metaphors and metonyms respectively. Colour metaphors are often based on learned associations of above mentioned ethnic groups, which contribute much to the way writers perceive and attach meanings to colours. Colour metonymies used in fiction add deeper symbolic meaning in the understanding of the literary characters and situations.
Keywords: colour terms; colour metaphor; colour metonymy; transfer of meaning; колороніми; кольорова метафора; кольорова метонімія; перенесення значення; кафедра іноземних мов професійного спрямування